The marzēaḥ in the prophetic literature : references and allusions in light of the extra-biblical evidence - McLaughlin, John L. (Supplements to Vetus Testamentum, 2001)
The marzēaḥ existed for 3000 years in the Semitic world, but is only mentioned in the First Testament at Amos 6:7 and Jer 16:5. Other prophetic texts have been proposed as allusions that do not use the term, but without using any consistent criteria. This study analyzes those allusions in light of the extra-biblical references. The extra-biblical marzēaḥ references indicate three consistent features: upper-class drinking within a religious context. These elements provide the minimum criteria for evaluating possible allusions in the books of Amos, Hosea, Isaiah and Ezekiel, plus the direct references at Amos 6:7 and Jeremiah 16:5. Combining all known references with the biblical allusions provides a single point of reference for future work on the marzēaḥ. This volume will be of special value to those interested in ancient Semitic religion.